Zeros of homothetic vector fields in 4-dimensional manifolds of neutral signature - KIRIK RÁCZ, BAHAR (My University, 2024)
This paper explores the situation regarding the zeros of a proper homothetic vector field X on a 4-dimensional manifold admitting a metric of neutral signature. The types of such zeros are described in terms of the algebraic types of the Ricci tensor and Weyl tensor at the said zero together with a geometrical description of the set of such zeros. A comparison is made between the situation occurring here and that for positive definite and Lorentz signatures. Examples are given to show that many of the theoretical possibilities derived for such zeros actually exist.
Keywords: Matematik; Fizik; Astronomi ve Astrofizik; Genel Fizik; Temel Bilimler; Mathematics; Physics; Astronomy and Astrophysics; General Physics; Natural Sciences; Temel Bilimler (SCI); Uzay bilimi; MATEMATİK; ASTRONOMİ VE ASTROFİZİK; FİZİK, MATEMATİK; Natural Sciences (SCI); MATHEMATICS; SPACE SCIENCE; PHYSICS; ASTRONOMY & ASTROPHYSICS; PHYSICS, MATHEMATICAL; Matematiksel Fizik; Fizik Bilimleri; Genel Fizik ve Astronomi; Geometri ve Topoloji; Mathematical Physics; Physical Sciences; General Physics and Astronomy; Geometry and Topology; Fixed points; Homotheties; Neutral signature; Symmetries